Perceived stress among employees of software companies in Romania, toward the COVID-19 Pandemic (International Journal of Scientific Research and Management (IJSRM), 2022)
The COVID-19 pandemic situation affected all the businesses and all the humans around the world. After the impact of the first pandemic months, the companies developed a set of knowledge and strategies for preventing the loss. At the same time, the population had to protect themselves and find a solution to the other emerging problems. One of the most common effects of the pandemic is the stress. The present study, aims to analyse the perceived stress level among employees of software companies acting in Romania using Pandemic-Related Perceived Stress Scale. The score registered in researched population was 14.140; that means that the perceived stress level is lower moderate. The female registered a higher score, 14.261, while the male registered 14.005, with a standard deviation of .204 and .075. Although there are differences between scores recorded by females and males, they are not significant.